A highly stretchable, self-healable, transparent and solid-state poly(ionic liquid) filler for high-performance dielectric elastomer actuators - Wang, Hui (2023)
By incorporating fillers into dielectric elastomers, electromechanical sensitivities can be enhanced to lower the required operating electrical field for actuation. However, existing solid and liquid fillers suffer from increased stiffness and filler leakage problems respectively, hindering the actuation performance of dielectric elastomer actuators (DEAs). To address these challenges, a soft, stretchable (∼300%), transparent (∼99%), and solid-state poly(ionic liquid) (PIL) is introduced to DEAs as a compliant filler. The mechanical properties of the PIL can be tuned by controlling the solvent ratio within precursors. When the PIL filler is introduced to a very high bonding elastomer (VHB), the effective dielectric constant increases from 4.7 to 16.4 at 1 kHz and the Young's modulus decreases to 0.21 MPa. The resulting planar DEA could achieve an area strain of 133% at 17 V μm−1, exceeding that of most DEAs with fillers. Notably, the PIL achieves adhesion and rapid self-healability, which eliminates filler leakage problems and endows DEAs with recoverability. A unimorph DEA demonstrates a bending angle of 44.7° at 12.6 V μm−1, two times greater than that exhibited by a DEA without the PIL filler. Simultaneous dynamic motion and light emission are further realized by integrating a unimorph DEA with an electroluminescent layer. Thus, the solid-state PIL filler provides high-performing and safer DEAs for soft robotics, interactive lighting, or wearables.